2005
DOI: 10.1007/s10551-004-3897-z
|View full text |Cite
|
Sign up to set email alerts
|

Everybody Else is Doing it, So Why Can?t We? Pluralistic Ignorance and Business Ethics Education

Abstract: In light of the myriad accounting and corporate ethics scandals of the early 21st century, many corporate leaders and management scholars believe that ethics education is an essential component in business school education. Despite a voluminous body of ethics education literature, few studies have found support for the effectiveness of changing an individual's ethical standards through programmatic ethics training. To address this gap in the ethics education literature the present study examines the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
0
37
0
1
Order By: Relevance
“…Jeff S. Everett first encountered in the classroom (on the efficacy of ethics education, see Bampton and Maclagan, 2005;Halbesleben et al, 2005). While some appeared to acquiesce to the implicit demands of neoclassical economic theory and thus limit their concern with what constitutes right action to the self-interest, the maximization of utility, or the avoidance of costs, others appeared to resist.…”
Section: Andmentioning
confidence: 99%
“…Jeff S. Everett first encountered in the classroom (on the efficacy of ethics education, see Bampton and Maclagan, 2005;Halbesleben et al, 2005). While some appeared to acquiesce to the implicit demands of neoclassical economic theory and thus limit their concern with what constitutes right action to the self-interest, the maximization of utility, or the avoidance of costs, others appeared to resist.…”
Section: Andmentioning
confidence: 99%
“…With students of a course in business ethics, Halbesleben et al (2005) empirically tested if the discussion about pluralistic ignorance and the reduction of it increased the patterns of concepts about ethical attitudes. They found that students who participated in the discussions about pluralistic ignorance were less likely to engage in unethical issues in today's business environment.…”
Section: Organizational Capabilitiesmentioning
confidence: 99%
“…In recent publications, it was highlighted that merely identifying the presence of an ethical situations is not enough (Halbesleben, Wheeler, & Buckley, 2005). This is because once they have identified and made their own ethical decision, they are hesitant to voice it out.…”
Section: Ethics and Educationmentioning
confidence: 99%
“…In simplicity, they are in favour a 'perceived opinion' to which everyone are actually opposed to. The term pluralistic ignorance is applied at this instance (Halbesleben, Wheeler, & Buckley, 2005). Going along this line, the moral reasoning judgement of an individual is constantly changing.…”
Section: Ethics and Educationmentioning
confidence: 99%